Khilāfah, Taskhīr, and Sustainability: Reconstructing Islamic Eco-Theology through Al-Qurțubī's Tafsir - Fahim Khasani (ISTIFHAM, 2025)
The contemporary ecological crisis—manifested through climate change, biodiversity loss, and environmental degradation—requires more than technological and political solutions; it demands ethical and spiritual renewal. This article examines the classical tafsir of al-Qurțubī  (d. 671 H) to explore Islamic environmental thought's theological and ethical foundations. Focusing on four key Qur'anic concepts—khalīfah fī al-ard (vicegerency), 'imārat al-ard (constructive inhabitation), taskhīr (divine subjugation of nature), and the prohibition of fasād (corruption)—this study demonstrates how al-Qurțubī formulated a coherent framework that positions humans as trustees, cultivators, grateful beneficiaries, and moral guardians of the earth. Using hermeneutical textual analysis and comparative readings with other classical exegetes (al-Ṭabarī, Fakhr al-Rāzī, Ibn Kathīr), the study identifies epistemological continuities between medieval interpretations and contemporary Islamic eco-theology. Thinkers like Seyyed Hossein Nasr, M. Izzi Deen, and Richard Foltz reinterpret these classical notions to address modern environmental challenges. The findings indicate that classical Islamic exegesis embeds a sophisticated environmental ethic emphasizing stewardship, sustainability, intergenerational justice, and spiritual accountability. Revisiting al-Qurțubī's tafsir offers historical insight and normative resources for constructing a contemporary Islamic environmental ethic. This framework can serve as an alternative paradigm in responding to the global ecological crisis by reaffirming the sacred interconnectedness between God, humanity, and nature.